2019
DOI: 10.3906/sag-1901-128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medial Olivocochlear Efferent System and Hearing Loss in Patients with Primary Sjögren's Syndrome

Abstract: Background/aim: Autoimmune diseases are a remarkable issue for researchers due to their adverse effects on the auditory system, but for primary Sjögren's syndrome (pSS) there is little research on the comprehensive audiological findings in literature. The main objective of this study was to investigate the medial olivocochlear efferent functions of subjects with pSS and to examine the audiological findings. Materials and methods: The study included 36 subjects with pSS and 36 healthy subjects. All the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…SjD and hearing loss Our study, using population-based data, shows that patients with SjD have a higher risk of hearing loss than those without SjD (AOR=1.724, 95% CI 1.598-1.859), which is consistent with other studies based on case reports and case series. Studies have shown that hearing loss, mainly sensorineural, but also conductive, 12 and mixed type hearing loss, 13 could be highly prevalent in patients with SjD, [13][14][15][16][17][18] with 4.5%-46% of patients with SjD showing SNHL 12 16 17 19-22 in line with our study finding of 5.6%. SNHL associated with SjD usually affects hearing of high frequency sounds (2 kHz-8 kHz).…”
Section: Discussionsupporting
confidence: 91%
“…SjD and hearing loss Our study, using population-based data, shows that patients with SjD have a higher risk of hearing loss than those without SjD (AOR=1.724, 95% CI 1.598-1.859), which is consistent with other studies based on case reports and case series. Studies have shown that hearing loss, mainly sensorineural, but also conductive, 12 and mixed type hearing loss, 13 could be highly prevalent in patients with SjD, [13][14][15][16][17][18] with 4.5%-46% of patients with SjD showing SNHL 12 16 17 19-22 in line with our study finding of 5.6%. SNHL associated with SjD usually affects hearing of high frequency sounds (2 kHz-8 kHz).…”
Section: Discussionsupporting
confidence: 91%